Development of Prosthetic Robotic Arm with Patient Monitoring System For Disabled Children; Preliminary Results - Babu, Devin; Abdul Nasir, Abd Ghafar; Farag, Mohannad; M. H., Muhammad Sidik (IEEE, 2022)
This paper describes the development of a prosthetic robotic arm with a patient monitoring system for disabled children. A prosthetic robotic arm helps disabled people increase their movement, manage their everyday activities, and maintain independence. Prosthetic arms currently on the market are prohibitively expensive for the financially disadvantaged and less user-friendly. This work aims to develop a low-cost, three dimensional (3D) prosthetic robotic hand that focuses on children. The prosthetic robotic arm was built using a compact microcontroller (ESP32). Every time the user desires to grasp and pick an object, the force sensor receives a signal of muscle flex activity. Besides that, the proposed robotic arm is equipped with a patient monitoring system consisting of a heartbeat tracker that measures the user's pulse, heartbeat, temperature, and location via a global positioning system (GPS). The prosthetic robotic hand lifted objects consisting of the cylindrical bottle up to 1 kg of weight, rectangular bottle up to 500 ml, and square bottle up to 300 ml. The patient monitoring system shows the temperature of 32.87 Celsius (C) and the user's pulse of 71 beats per minute (bpm) in the monitoring GUI.